Regulation of water, salinity, and cold stress responses by salicylic acid - Miura, Kenji; Tada, Yasuomi (Frontiers in Plant Science, 2014)
Salicylic acid (SA) is a naturally occurring phenolic compound. SA plays an important role in the regulation of plant growth, development, ripening, and defense responses. The role of SA in the plant-pathogen relationship has been extensively investigated. In addition to defense responses, SA plays an important role in the response to abiotic stresses, including drought, low temperature, and salinity stresses. It has been suggested that SA has great agronomic potential to improve the stress tolerance of agriculturally important crops. However, the utility of SA is dependent on the concentration of the applied SA, the mode of application, and the state of the plants (e.g., developmental stage and acclimation). Generally, low concentrations of applied SA alleviate the sensitivity to abiotic stresses, and high concentrations of applied induce high levels of oxidative stress, leading to a decreased tolerance to abiotic stresses. In this chapter, the effects of SA on the water stress responses and regulation of stomatal closure are reviewed.